The Visual Analysis of a Stool Design with a Combination of Rattan and Iron Materials - Nurul Fitriana Bahri; Yoga Pujiraharjo; Sheila Andita Putri; Rizky Setya Hanugraha (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2026)
Furniture design in school environments plays a significant role in supporting comfort and functionality of spaces. One example of furniture that stands out is the bench made of a combination of rattan and metal, placed outside classrooms for students to wait while performing wudhu. This study aims to analyze the design of the bench at SDN 151 Sukasenang Bandung from a visual analysis perspective. A descriptive qualitative method was employed, utilizing observation of design elements such as form, texture, proportion, and material usage. The study found that the combination of rattan and metal creates a design that is not only aesthetically pleasing but also functional, providing comfort for users while waiting their turn for wudhu. This research also offers insights into how the appropriate choice of materials can enhance both aesthetics and comfort in outdoor areas used for social activities.